Evaluation of balanced fertilizer types on yield and yield components of sorghum and validation of soil fertility map based fertilizer recommendation - Robe Elema Wako; Ibsa Aliyi Usmane (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2020)
Sorghum has tremendous uses for the Ethiopian farmer and no part of this plant is ignored. However, the productivity of sorghum is low. In Harari region, the average productivity of 22.22 Quintal ha-1 which is even below the national average yield of 27.26 Quintal ha-1 mainly constrained by soil nutrient deficiencies. Soil fertility depletion in agricultural land is the fundamental biophysical root cause of declining per capita food production. So balanced fertilizer amended with enough amount of Nitrogen and phosphorous on sorghum gave the highest yield, nutritional content and economic return. Soil fertility map of Ethiopia was conducted during 2016 by ATA (Agricultural transformation Agency) .So this fertility map should be validated. Therefore, a field experiment was conducted during 2018 and 2019 main cropping season at Kile PA, Sofi woreda of Harari Regional state under rain-fed condition on balanced fertilizer types. The objectives of the experiment was to evaluate sorghum crop response to different balanced fertilizer types and validate soil fertility map based fertilizer recommendation. And to identify effects of different balanced fertilizer on yield and yield components of sorghum crop. The experiment was laid out in randomized complete block design with three replications. The treatments of this experiment were: control without any fertilizer (no fertilizer applied), NPS, NPSB, NPSZn, NPSZnB, DAP and Urea. The result shows significant difference among the treatments (P<0.05). Analysis of variance was performed using the GLM procedure of SAS Statistical Software Version 9.1.And partial budget analysis was conducted based on CIMMYT procedure [1]. Out of five balanced fertilizer types applied, NPSzn balanced fertilizer type shows the highest significant difference (P<0.05). The highest result of both sorghum grain yield and yield components was obtained from treatments that receive NPSzn fertilizer (52qu/ha) and the lowest grain and biomass yield was obtained from control with no fertilizer (25.48quntal/ha) followed by DAP and urea. Next to grain yield, biomass yield of sorghum is very important parameter that should be considered for the sake of animal feed in the Harari region (kile PA). So, the treatments that receive NPSZn balanced fertilizer shows the highest biomass yield (11.666t/ha).Thus why NPSZn fertilizer is valid for kile PA. Partial budget analysis was conducted and treatments with NPSZn balanced fertilizer was economically profitable for farmers. Mean that, farmers can obtain 39,134 Ethiopian birr/ha by applying NPSZn balanced fertilizer, over the control (with no fertilizer) 17186 Ethiopian birr/ha and the rest treatments.